Developing E-Commerce for Micro Small Medium Enterprise (MSME) to Cope with Cultural Transformation of Online Shopping - Prameswari, Nadia Sigi; Suharto, Mohamad; Afatara, Narsen (JDM (Jurnal Dinamika Manajemen), 2017)
This study aims to examine factors contributing to societies’ tendencies to choose online shopping, the characteristics of e-commerce needed by societies and obstacles faced by MSME in handling business competition. E-commerce is a set of dynamic technology, application and business process which connects certain companies, consumers and communities through electronic transaction. Trade of goods, services and information is performed electronically. The development of E-commerce system for MSME aims to change its culture which still relies on conventional purchasing into online shopping, improve MSME’s sales in order to promote, market and sell products to internet users through website without any space and time limits. The research subjects are people involving in MSME and communities of Jebres village, Surakarta. This study applies qualitative paradigm. The research subjects were taken using purposive sampling techniques. Data were collected using various techniques: structured interview, questionnaire, observation and content analysis or archive analysis. Data were later analyzed using four stages, namely data reduction, classification, data presentation and verification.